Pain after laparoscopic cholecystectomy: Effect of local anesthesia - (:unkn) unknown (AVES, 1994)
Effect of local infiltration anesthesia on postoperative laparoscopic cholecystectomy patients have been studied. A prospective study was done. 25 patients received local anesthesia (Bupivacaine) infiltration around the port sites and another 25 patients received 0.9% NaCl infiltration as the control group. Pain scoring was done with '0-10 Numeric Pain Distress Scale' in the postoperative hours. According to the results, local anesthetic infiltration around the port sites significantly decreases postoperative pain in laparoscopic cholecystectomy patients.
Keywords: Laparoscopic cholecystectomy; Pain